Muscle-Bone Crosstalk in Chronic Obstructive Pulmonary Disease - Zhang, Lijiao; Sun, Yongchang (Frontiers in Endocrinology, 2021)
Sarcopenia and osteoporosis are common musculoskeletal comorbidities of chronic obstructive pulmonary disease(COPD) that seriously affect the quality of life and prognosis of the patient. In addition to spatially mechanical interactions, muscle and bone can also serve as endocrine organs by producing myokines and osteokines to regulate muscle and bone functions, respectively. As positive and negative regulators of skeletal muscles, the myokines irisin and myostatin not only promote/inhibit the differentiation and growth of skeletal muscles, but also regulate bone metabolism. Both irisin and myostatin have been shown to be dysregulated and associated with exercise and skeletal muscle dysfuntion in COPD. During exercise, skeletal muscles produce a large amount of IL-6 which acts as a myokine, exerting at least two different conflicting functions depending on physiological or pathological conditions. Remarkably, IL-6 is highly expressed in COPD, and considered to be a biomarker of systemic inflammation, which is associated with both sarcopenia and bone loss. For osteokines, receptor activator of nuclear factor kappa-B ligand (RANKL), a classical regulator of bone metabolism, was recently found to play a critical role in skeletal muscle atrophy induced by chronic cigarette smoke (CS) exposure. In this focused review, we described evidence for myokines and osteokines in the pathogenesis of skeletal muscle dysfunction/sarcopenia and osteoporosis in COPD, and proposed muscle-bone crosstalk as an important mechanism underlying the coexistence of muscle and bone diseases in COPD.